Is it possible to predict late antepartum stillbirth by means of cerebroplacental ratio and maternal characteristics?. (1st September 2020) - Morales-Roselló, José; Galindo, Alberto; Herraiz, Ignacio; Gil, María M.; Brik, Maia; De Paco-Matallana, Catalina; Ciammela, Ricardo; Sanchez Ajenjo, Carlos; Cañada Martinez, Antonio José; Delgado, Juan Luis; Perales-Marín, Alfredo; ,
Abstract: Objective: To examine the potential value of fetal ultrasound and maternal characteristics in the prediction of antepartum stillbirth after 32 weeks' gestation. Methods: This was a retrospective multicenter study in Spain. In 29 pregnancies, umbilical artery pulsatility index (UA PI), middle cerebral artery pulsatility index (MCA PI), cerebroplacental ratio (CPR), estimated fetal weight (EFW), and maternal characteristics were recorded within 15 days prior to a stillbirth. The values of UA PI, MCA PI, and CPR were converted into multiples of the normal median (MoM) for gestational age and the EFW was expressed as percentile according to a Spanish reference range for gestational age. Data from the 29 pregnancies with stillbirths and 2298 control pregnancies resulting in livebirths were compared and multivariate logistic regression analysis was used to determine significant predictors of stillbirth. Results: The only significant predictor of stillbirth was CPR (OR = 0.161, 95% confidence interval [CI] 0.035, 0.654; p = .014); the area under the receiver operating characteristics curve was 0.663 (95% CI 0.545, 0.782) and the detection rate (DR) was 32.14% at a 10% false-positive rate (FPR). In addition, when we included MCA and UA PI MoM instead of CPR, only MCA PI MoM was significant (OR = 0.104, 95% confidence interval [CI] 0.013, 0.735; p = .029), with similar prediction abilities (area under the curve (AUC) 0.645, DR 28.6%, FPR 10%). Conclusions: The CPR and MCA PI are predictors of late stillbirth but the performance of prediction is poor.